Climate change, agriculture, and adaptation options for Peru - Gianella, Cecilia; Chavez-Tafur, Jorge; Thomas, Timothy S. (International Food Policy Research Institute, 2019)
While agriculture represents only 7 percent of total GDP (World Bank 2014) for Peru, it is not an insignificant economic sector. It provides employment for 26 percent of the population (World Bank 2014) and is an important potential engine for poverty reduction in Peru. Because climate change has a large potential impact on the agriculture sector, the analysis done in this paper using climate models, crop models, and a bioeconomic model provides important information to those concerned with planning and investing for the future. Our study shows a relatively positive outlook for agriculture in Peru compared to the rest of the world. Crop model analysis suggests that climate change will actually improve yields for rice, barley, wheat, cassava, and irrigated maize. Rainfed maize would experience some modest yield reductions and sugarcane would experience some large yield reductions, though compared to the rest of the world, the reductions appear manageable. While not directly measured by crop models, comparing to similar crops that were modeled, it appears that potatoes and plantains will also be favored by climate change. In addition to sugarcane, this discussion paper discusses the likely impact on coffee production and suggests some positive steps that could be taken to mitigate some of the impact. The paper also discusses the potential adverse effects on livestock productivity, and what might be done to reduce them. Finally, the paper considers the spatially heterogenous effects of climate change on agriculture, pointing to areas that benefit and others that are harmed. Such details could help develop responses to climate change suitable to each region.